Historia, historiografía y género. Notas para la memoria de sus vínculos en la Argentina - Barrancos, Dora (Revista de Historia Social y de las Mentalidades, 2025)
This study examines connections between court cases of family conflicts in nineteenth century Buenos Aires and the world of jurisprudence. Although many colonial laws continued in place after independence, the attitudes of many judges’, lawyers’, and politicians’ toward those laws changed. The result was a shift in interpretation and application of the old laws, a shift that affected the daily lives of many porteños during the nation building process.
Keywords: History; Women Historiography; gender